ЁШ КУРАШЧИЛАРГА ТЕХНИК ВА ТАКТИК ҲАРАКАТЛАРНИ ЎРГАТИШДА ЖИСМОНИЙ МАШҚЛАРДАН ФОЙДАЛАНИШ УСЛУБЛАРИ - Нурышов, Д.; Есемуратов, С. (SCIENCE and SOCIETY, 2016)
The article is devoted to the issues of technical and tactical development of young sportsmen who go in for such kind of sport as kurash (fight).
Keywords: kurash; technique and tactics; general developing exercises; strength-power training; endurance; nimbleness; speed